Cardiovascular co-morbidity in cancer patients: the role of psychological distress. Issue 1 (December 2016) - Schoormans, Dounya; Pedersen, Susanne; Dalton, Susanne; Rottmann, Nina; van de Poll-Franse, Lonneke
Abstract Due to aging of the population and cardiotoxic cancer treatment, there is an increasing group of patients with cancer and co-morbid cardiovascular disease (CVD). In order to find a balance between the risk of undertreating the malignancy on the one hand and inducing CVD on the other hand, CVD risk stratification at the time of cancer diagnosis and knowledge on the pathway for developing incident CVD in cancer patients is vital. In this paper, we propose an adapted multiple-hit hypothesis for developing CVD in cancer patients describing that patients with cancer are exposed to a series of sequential or concurrent events that together make them more vulnerable to reduced cardiovascular reserves, development of incident CVD and ultimately death. We highlight the possible impact of psychological distress secondary to a cancer diagnosis and/or treatment, which in turn may increase the risk of incident CVD in patients diagnosed with cancer. Furthermore, we discuss potential behavioral and pathophysiological mechanisms underlying the link between psychological distress and the pathophysiology of incident CVD. In addition, key unanswered questions for future research are posed. In the future, researching the adapted multiple-hit hypothesis for developing CVD among cancer patients will hopefully advance the care of cancer patients by finding some of the missing pieces of the puzzle. To do so, we need to focus on minimizing cardiovascular risk and promoting cardiovascular health in cancer patients by addressing the knowledge gaps formulated in this paper.